TRACKING ON MODERATE MUSLIM IN INDONESIA - Syafwan Rozi (Turast: Jurnal Penelitian dan Pengabdian, 2014)
This study focuses on tracking the dynamics of Indonesian conversations on moderate Islam thought. It attempts toanswer number of questions concerning with the base and background of moderate Islam in developing its ideologybetween fundamentalism and liberalism pattern, form and typology and the development of moderate Islam movementin Indonesia. For this objectives, this study examines the role of the moderate Islam institution in Indonesia. This studyshows that Muslim thinkers have made some of the greatest intellectual and theoretical contributions to the debatesover Islam and human rights, Islam and democracy, and Islam and women’s rights. This position is in line with thestate concerns. This means that Moderate Islam in Indonesia has provided the foundations of civil society that madethe transition to democracy possible whereas in the Middle East Islam has been seen as anathema to democratization.